Evidence for Pharmacological Management in Delirium - Grover, S.; Mattoo, S. K.; Gupta, N. (Pharmacopsychiatry, 2012)
There is limited evidence about the usefulness of antipsychotics and choline esterase inhibitors in delirium. There are very few placebo controlled trials. There is a need to conduct well designed trials to evaluate the efficacy of antipsychotics and choline esterase inhibitors in delirium.
Keywords: delirium; electroconvulsive therapy (ECT); drug interaction